The Relationship Between Age, Body Weight, And Gestational Hypertension In Second Trimester Pregnant Women At The Ngembal Kulon Community Health Center - Dilla Oktavia Stifani; Noor Hidayah; Umi Faridah (International Journal of Health Engineering and Technology, 2026)
Gestational hypertension is a major pregnancy complication with a prevalence of 6.18% in Indonesia (RISKESDAS 2018), influenced by age at risk and obesity, but local data from the Ngembal Kulon Community Health Center is limited. This study aims to analyze the relationship between age and body weight (BMI) with gestational hypertension in second-trimester pregnant women. This type of quantitative analytical observational case-control study was conducted on the population of second-trimester pregnant women at the Ngembal Kulon Community Health Center from January to February 2026 with a sample of 60 total sampling respondents (case:control ratio 1:2). Digital sphygmomanometer instruments and digital scales were analyzed univariately (frequency, mean) and bivariately (Chi-Square, OR) via SPSS (α = 0.05). The results showed a prevalence of 33.3%; At-risk age (≤20/≥35 years, 35%) was dominant in cases (76.2%, OR=28, p=0.000) and overweight-obesity (BMI≥25, 33.3%) in 75% of cases (OR=0.048, p=0.000). The conclusion that at-risk age and overweight-obesity were significantly associated with gestational hypertension recommends routine ANC screening and nutrition education.